Conversion of alcohols to olefins and ethers on supported and unsupported metal phosphate catalysts - Lau, Mei Hui. (2009)
P modified ZSM-5 catalysts were prepared by incipient wetness method with varying H3PO4 content from 5 to 20 wt% which yield the P content between 0 to 7.46 wt%. The catalysts were evaluated towards ethanol dehydration at 250-450 °C and butanol dehydration at 200-350 °C. The catalysts were thoroughly characterized by N2 physisorption, XRD, NH3-TPD, FTIR, 1H, 27Al, 29Si, and 31P MAS NMR. The characterization results indicate the effect of pore blockage and modification of weak acidic sites strength increase with P loading. Hence, the activity and stability of catalysts in alcohol conversion to light olefins is improved. In addition, nanostructured LaPO4 with P/La of 0.5, 1.0, 1.5 and 2.0 were prepared by sol-gel method using La(NO)3 .6H2O and NH4H2PO4 as precursors. The activity of catalysts for ethanol dehydration was determined at between 250-450 °C while 200-350 °C for butanol dehydration. The catalysts were characterized by N2 physisorption, XRD, NH3-TPD, FT-IR, RAMAN and SEM. The surface area of LaPO4 with higher P/La increases due to the formation of fiber-shaped surface as shown by SEM images. Suppressing of strong acidic sites and enhancing strength of weak acidic sites by increasing P/La, can improve the selectivity to light olefins and decrease the formation of aromatics. The alcohol dehydration over these two categories of catalysts follows literature-reported dehydration mechanisms, where ethers are favorable at low temperature whereas light olefins are predominant at high temperature. Exceptional case is butanol dehydration over 2.0LaPO4 as the formation of butylenes is favored over ethers.